Economic analysis of normative versus practical manegement of coniferous stands in Lithuania - Jasinevicius, Gediminas (SLU/Southern Swedish Forest Research Centre, 2008)
Economic outcomes from a particular forest stand depend on many factors but the underlying cause is the prevailing silvicultural practices, following management regulations and tradition. This study examines Scots pine and Norway spruce stands of average productivity in Lithuania. The findings of the study revealed considerable differences between theoretical program developed according to management regulations and practical forest management in situ. Discrepancy between theoretical and practical forest management leads to the uncertain forest economy, and decision making. Another factor having considerable effect on economic outcomes is wood prices and producing costs. After a huge jump in wood prices over the last two years, economic indicators have significantly changed. This fact indicates uncertainty that has to be considered in the longterm forestry projects. Economic outcomes were calculated employing methodologies that are widely used in the Nordic countries. In Scandinavia the model of costs and income discounting is present that makes it possible to pursue economically efficient forestry. In Lithuania various methods of calculating economic outcomes without discounting are still used that pursues traditional forestry (based on maximum possible volume of certain assortments at the age of final felling). As a part of methodology a survey was carried out with the aim to investigate practical forest management in Lithuania. Results of this study can be used for comparative analyzes with other countries in Baltic Sea region.